Support the use of artificial intelligence tools and reduce its harm - Dhay Abdullateef Hammood Aljasim (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
The goal of this study is to look into ways to support the good use of artificial intelligence (AI) tools while minimizing the potential harm they can cause to people and society. A sample of 153 people from various professional and public backgrounds participated in the study. A structured questionnaire was used to test a main hypothesis and three sub-hypotheses related to ethical guidelines, regulatory oversight, and educational awareness as ways to reduce AI-related risks using a quantitative methodology. Participants were unanimous in their belief that ethical frameworks, clear legal regulations, and increased education and training are necessary for the responsible integration of AI technologies, according to the findings. More specifically, more than 84% of respondents agreed that education and awareness play a crucial role in ensuring AI safety, while approximately 77% emphasized the significance of regulatory oversight. The main hypothesis, which is that AI harms can be significantly reduced by combining ethics, law, and education, is supported by these outcomes. The study recommends expanding educational programs, establishing enforceable regulatory frameworks, and adopting comprehensive ethical standards to improve public and professional understanding of AI. To promote public confidence in AI systems and strike a balance between innovation and safety, such an integrated approach is essential.